2014
DOI: 10.1371/journal.pntd.0003045
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Circulation of the Rift Valley Fever Virus among Livestock in the Union of Comoros

Abstract: Rift Valley fever virus (RVFV) is an arthropod-borne phlebovirus reported to be circulating in most parts of Africa. Since 2009, RVFV has been suspected of continuously circulating in the Union of Comoros. To estimate the incidence of RVFV antibody acquisition in the Comorian ruminant population, 191 young goats and cattle were selected in six distinct zones and sampled periodically from April 2010 to August 2011. We found an estimated incidence of RVFV antibody acquisition of 17.5% (95% confidence interval (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…These results confirm the only suspicion going back to 2007 when an autochthonous clinical case of RVFV was detected in a child from Ngazidja admitted at Mayotte’s hospital with a 2-month history of severe encephalitis [28]. They are also coherent with the demonstration of an active circulation of the virus in Comorian livestock [29,30]. With regard to Mayotte, an investigation carried out on 2007–2008 on dengue-like syndromes, testing negative for Plasmodium spp., CHIKV, and DENV, revealed 4.5% positive cases, suggestive of recent RVFV infection, i .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These results confirm the only suspicion going back to 2007 when an autochthonous clinical case of RVFV was detected in a child from Ngazidja admitted at Mayotte’s hospital with a 2-month history of severe encephalitis [28]. They are also coherent with the demonstration of an active circulation of the virus in Comorian livestock [29,30]. With regard to Mayotte, an investigation carried out on 2007–2008 on dengue-like syndromes, testing negative for Plasmodium spp., CHIKV, and DENV, revealed 4.5% positive cases, suggestive of recent RVFV infection, i .…”
Section: Discussionsupporting
confidence: 76%
“…Similarly, the higher IgG seropositivity rates to CHIKV, DENV and RVFV measured on Ngazidja in the present study may simply reflect this geographical proximity. However, the higher IgM positivity rates to RVFV in sera from Mwali is in keeping with the fact that livestock was mostly infected on Mwali [29,30]. …”
Section: Discussionmentioning
confidence: 90%
“…A similar result was found in a serological survey of anti-RVFPV antibodies in Tanzania where 25.8% (n = 1435) of domestic ruminants (sheep, cattle and goats) were seropositive [47]. The seroprevalence found in this study was higher than that found in cattle and goats in the Union of Comoros (17.5%; n = 191), between 2010–2011 [48]. …”
Section: Discussionsupporting
confidence: 88%
“…Such a discrepancy is likely to result from space scale sampling differences: our estimation was done at the eco-regional level whereas the other one was performed in a district highly affected by RVF in 20081219. Two studies performed in the tropical islands of the South-West Indian Ocean showed an annual RVFV antibody acquisition about 17.5% in Union of Comoros in 2010–1143 and an IgM prevalence about 4% in 2010–11 in Mayotte44, which were higher than our estimations. Yet, the climatic situations in the Union of Comoros and Mayotte, under marine tropical conditions, are extremely different than in Madagascar.…”
Section: Discussionmentioning
confidence: 98%
“…Yet, the climatic situations in the Union of Comoros and Mayotte, under marine tropical conditions, are extremely different than in Madagascar. Furthermore, since 2002, importation of live animals from Tanzania is frequent in the Union of Comoros and could then increase the risk of RVFV circulation43. In the semi-arid area of the Barkedji region of Senegal, studies showed a seroconversion rate among monitored small ruminants of 1.9% between of 1991–93 and 2.9% during the rainy season of 20034546.…”
Section: Discussionmentioning
confidence: 99%